Lumbar Disc Herniation Might Spontaneously Regress, While Neuropathic Pain Might Start: Retrospective Clinical Study - Yener Akyuva; Necati Kaplan; Boran Urfalı; Özkan Özger; Erdinç Civelek; Serdar Kabataş; Yurdal Serarslan (Turkish Journal of Agriculture: Food Science and Technology, 2020)
Lumbar disc herniation (LDH) is a common cause of low back pain and radicular pain. The aim of our study was to evaluate the regression of LDH in patients who are considered to require surgical treatment but prefer conservative treatment. Patients who presented between January 2018 and June 2020 and who did not accept the recommended surgical treatment following a diagnosis of LDH based on clinical and radiological findings were retrospectively reviewed. All 12 of the patients included in the study showed spontaneous regression of LDH during outpatient clinical follow-up. Our study included 12 patients (seven male and five female). The mean age was 46.5 (the youngest was 30 years old; the oldest was 70 years old). Regression was observed at the L2-L3 level in two patients (10%), at the L4-L5 level in four patients (40%), and at the L5-S1 level in six patients (50%). On the follow-up examination of all patients, the severity of their pain was evaluated with the Visual Analogue Scale, and all patients described a reduction in pain (min: 2, max: 8). Ten patients described radicular pain at the initial examination, eight patients received physical therapy and rehabilitation treatment before the follow-up examination, and nine patients described neuropathic pain at the follow-up examination. Spontaneous regression of LDH is rare. While conservative treatments provided partial improvement in the complaints of these patients, conservative treatments usually cannot prevent the development of neuropathic pain.